A new thermodynamic model for sapphirine: calculated phase equilibria in K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–Fe2O3. (10th February 2014) - Wheller, C. J.; Powell, R.
Abstract The activity–composition (a–x) relations of sapphirine are re‐evaluated in the light of a recent new internally‐consistent data set of phase end‐members for use in phase equilibria modelling, particularly of ultra‐high‐temperature (UHT) rocks. This is achieved with the aid of relatively oxidized sapphirine+quartz‐bearing granulites from Wilson Lake, Canada. Calculated P–T projections and compatibility diagrams in the K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–Fe2O3 (KFMASHTO) system are used to illustrate sapphirine+quartz‐bearing phase equilibria in the context of UHT metamorphism. These new a–x relations for sapphirine should allow pseudosection thermobarometry in NCKFMASHTO for estimating peak P–T conditions of sapphirine‐bearing rocks.